2015
DOI: 10.1016/j.ultsonch.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration kinetics of salmon and trout fillets using ultrasonic vacuum drying as a novel technique

Abstract: In this study, a novel ultrasonic vacuum (USV) drying technique was used to shorten the drying time of fish fillets. For this purpose, ultrasonic treatment and vacuum-drying were simultaneously performed to dehydrate salmon and trout fillets at 55°C, 65°C, and 75°C. In addition, the USV technique was compared with vacuum-drying and oven-drying techniques. The dehydration kinetics of the fillets was successfully described by seven thin-layer drying models with R(2) range between 0.944 and 1.000. Depending on dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 35 publications
12
30
1
Order By: Relevance
“…The values of R 2 (>0.9676), of χ 2 (<0.0032), and of RMSE (<0.2506) presented in Table 2 indicate that, overall, all models tested are able to predict, with good precision, the dehydration kinetics of tilapia cubes in the different conditions studied. However, the Page model had the best fit to all studied treatments (R 2 = 0.9889-0.9977; χ 2 = 0.0005-0.0020; RMSE = 0.0700-0.1280), in accordance with the studies of hot air drying of thin-layer fresh tilapia fillets (Ponwiboon & Rojanakorn, 2017), drying of titus fish fillets using an indirect passive hybrid solar-charcoal smoke dryer (Nwakuba, Okafor, Abba, & Nwandikom, 2018), as well as drying salmon and trout fillets using oven drying (Başlar et al, 2015). Table 3 shows the chemical composition of the dehydrated tilapia cubes by the effect of the ultrasound treatment.…”
Section: Dehydration Kineticssupporting
confidence: 82%
See 2 more Smart Citations
“…The values of R 2 (>0.9676), of χ 2 (<0.0032), and of RMSE (<0.2506) presented in Table 2 indicate that, overall, all models tested are able to predict, with good precision, the dehydration kinetics of tilapia cubes in the different conditions studied. However, the Page model had the best fit to all studied treatments (R 2 = 0.9889-0.9977; χ 2 = 0.0005-0.0020; RMSE = 0.0700-0.1280), in accordance with the studies of hot air drying of thin-layer fresh tilapia fillets (Ponwiboon & Rojanakorn, 2017), drying of titus fish fillets using an indirect passive hybrid solar-charcoal smoke dryer (Nwakuba, Okafor, Abba, & Nwandikom, 2018), as well as drying salmon and trout fillets using oven drying (Başlar et al, 2015). Table 3 shows the chemical composition of the dehydrated tilapia cubes by the effect of the ultrasound treatment.…”
Section: Dehydration Kineticssupporting
confidence: 82%
“…At the initial stage of the dehydration process, the moisture movement is rapid because of the evaporation of moisture at the product's surface. However, it decreases exponentially while dehydration because of the difficulty of the transport of the evaporated water through material (Başlar et al, 2015), as was observed in this study. On the other hand, power ultrasound is an emerging technology that can induce chemical, biological and mechanical changes in meat due to cavitation in liquid systems, which contribute to accelerated mass transport (Kang, Gao, Ge, Zhou, & Zhang, 2017).…”
Section: Dehydration Kineticssupporting
confidence: 66%
See 1 more Smart Citation
“…The USV system is a combination of an ultrasound water bath (Daihan, WUC‐D10H, South Korea) (amplitude: 100%, power intensity: ∼1 W/cm 2 , volume: 10 L) and a vacuum pump (KNF N838.3KT.45.18, Germany) (pressure: 15 mbar speed: 22 L/min). This system was detailed in our previous published studies (Başlar, Kilicli, et al, 2014; Başlar, Kiliçli, & Yalinkiliç, ). The green beans samples were put into a conical flask attached to the vacuum pump and sonicated at 40 kHz by using the ultrasonic water bath.…”
Section: Methodsmentioning
confidence: 99%
“…The increase in the pirarucu farming in aquaculture production systems has highlighted the economic significance of this species in recent years, mainly due to its nutritional quality. However, its marketing and consumption throughout the year faces some barriers due to the many changes occurring in the product because of enzyme and microbiological activities, which can affect the flavor, odor, color and texture and lead to rapid deterioration, resulting in fish of lower quality [7,8].…”
Section: Introductionmentioning
confidence: 99%